Analisis Strategi Perubahan Visi dan Misi Perusahaan sebagai Bagian Adaptasi Pasar demi Keberlangsungan Bisnis pada Industri Manufaktur, Studi Kasus pada PT XYZ yang Mengolah Bahan Baku Utama Diamond (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This research aims to analyze the strategy of changing the company's vision and mission as part of market adaptation for business continuity, using the ADKAR change model. The method used is descriptive qualitative, a research whose description form uses facts or phenomena. This research was conducted in two stages, namely collecting information and literature on changes in the organization's mission and vision, business continuity, and identifying the change management model to be used in the research. Furthermore, data was collected from the results of interviews and participatory observation. The results showed that the purpose and message of organizational change must be clearly informed, why change must occur, and why change is needed. Change leaders must have good skills and knowledge about the planned changes. Change does not have to change the entire system that is already operating, changes can be made by using existing systems and resources to be optimized in achieving the new vision and mission. Using the ADKAR model in interview guidelines and discussing research results makes it easier to analyze the stages of change, so the ADKAR change model can be used as a reference when planning organizational change initiatives.